Answer:
![9y+2y-5y=6y](https://tex.z-dn.net/?f=9y%2B2y-5y%3D6y)
Step-by-step explanation:
So we have the expression:
![9y+2y-5y](https://tex.z-dn.net/?f=9y%2B2y-5y)
To simplify, simply combine the like terms. Therefore:
![9y+2y-5y\\=11y-5y\\=6y](https://tex.z-dn.net/?f=9y%2B2y-5y%5C%5C%3D11y-5y%5C%5C%3D6y)
Further notes:
To understand why we can combine like terms in the first place, we just need to use the distributive property. So we have the expression:
![9y+2y-5y](https://tex.z-dn.net/?f=9y%2B2y-5y)
Now, factor out a y from the three terms:
![=y(9+2-5)](https://tex.z-dn.net/?f=%3Dy%289%2B2-5%29)
Do all the operations inside the parenthesis:
![y(9+2-5)\\=y(11-5)\\=y(6)=6y](https://tex.z-dn.net/?f=y%289%2B2-5%29%5C%5C%3Dy%2811-5%29%5C%5C%3Dy%286%29%3D6y)
And we moved the y back to the front!
This is the same result as before. When combining like terms, this is what we're essentially doing but without doing the distributive property manually. I hope you understand a bit better on how and why we can combine like terms!
Answer:
i dont speak spanish sry
Step-by-step explanation:
but if you put it in english i would help
First off you need to multiply 6 by 3 for how many miles she went and then divide the leftover total by two (For the last two hours) to realize she needs to run 4.1 mph.
Hope this helped :)
F(-1) = -11
f(0) = -9
f(3) = -3